The Role of Knowledge Capital Development in the Effectiveness of Strategic Information Systems - علي ديب كندة (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The research sought to examine the relationship between knowledge capital development on the one hand, and between effectiveness of strategic information systems in the Telecom company-Syriatel on the other hand. The researcher relied on five dimensions of knowledge capital development(attracting knowledge capital- making knowledge capital- activating knowledge capital - preserving knowledge capital - attention to customer capital) and two dimensions of the effectiveness of strategic information systems (information value - individual performance of the employee), since the researcher distributed (220) questionnaire on a sample of syriatel employees, (150) responses were received, and(130) questionnaire were used for analysis. To test the relationship, the researcher used the T- student test for one sample, as well as the Pearson correlation coefficient. The research concluded that there is a increase in the level each of(attracting knowledge capital- making knowledge capital- activating knowledge capital - preserving knowledge capital - attention to customer capital) and a decrease in the level each of (information value - individual performance of the employee) in the company under study. The research also found a significant relationship between knowledge capital development and effectiveness of strategic information systems in Syriatel, and thus there is a role of knowledge capital development in the effectiveness of strategic information systems. The research concluded with a set of recommendations related to strengthening the cognitive capabilities of employees, and the need to adopt a clear strategy for building strategic information systems resources.